2002
DOI: 10.1073/pnas.0136820100
|View full text |Cite
|
Sign up to set email alerts
|

Quantum-mechanical calculations of the stabilities of fluxional isomers of C 4 H\documentclass[12pt]{minimal}\usepackage{amsmath}\usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy}\usepackage{mathrsfs}\setlength{\oddsidemargin}{-69pt}\begin{document}\begin{equation*}{\mathrm{_{7}^{+}}}\end{equation*}\end{document} in solution

Abstract: Although numerous quantum calculations have been made over the years of the stabilities of the fluxional isomers of C 4 H 7 ؉ , none have been reported for other than the gas phase (which is unrealistic for these ionic species) that exhibit exceptional fluxional properties in solution. To be sure, quantum-mechanical calculations for solutions are subject to substantial uncertainties, but nonetheless it is important to see whether the trends seen for the gas-phase C 4H7 ؉ species are also found in calculations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 21 publications
(13 reference statements)
3
45
0
Order By: Relevance
“…4−8 Cation 2 consists of three distinct, rapidly equilibrating isomers, including a bisected cyclopropylcarbinyl cation 2a, a symmetric bicyclobutonium ion 2b, and an unsymmetric bicyclobutonium ion 2c. 9 The equilibration of these structures is so fast that attempts to generate the homoallylic cation, cyclobutylcarbenium ion, or the cyclopropylcarbinyl cation each produce the same mixture of stable products. 10 State of the art calculations are in good general agreement with experimental data on these species.…”
mentioning
confidence: 99%
“…4−8 Cation 2 consists of three distinct, rapidly equilibrating isomers, including a bisected cyclopropylcarbinyl cation 2a, a symmetric bicyclobutonium ion 2b, and an unsymmetric bicyclobutonium ion 2c. 9 The equilibration of these structures is so fast that attempts to generate the homoallylic cation, cyclobutylcarbenium ion, or the cyclopropylcarbinyl cation each produce the same mixture of stable products. 10 State of the art calculations are in good general agreement with experimental data on these species.…”
mentioning
confidence: 99%
“…Moreover, it appears that MP2 often tends to overestimate the stability of 'nonclassical' structures. 17 While 1 and 2 were viewed as unsymmetrical species by Casanova et al 4 , we found that OPT=TIGHT calculations yielded geometries that were extremely close to the C S structures. Consequently we fixed the symmetry -in our case using Chemcraft 18 -to C S as did Olah et al…”
Section: Ch 3mentioning
confidence: 60%
“…Computational studies were also carried out in solvent fields. 4 The main focus of the most recent study on 2 and 3 carried out by Olah et al at various levels, including MP4(SDTQ)/cc-pVTZ//MP2/cc-pVTZ + ZPE was the calculation of 13 C NMR chemical shifts at CCSD(T). 1 With the exception of Brown's proposal 5 based on solvolysis data the cation should be viewed as a distorted cyclobutyl cation represented as 5, dashed-line or solid-line structures have been used to represent the bonding of these alleged nonclassical pentacoordinate species in all the studies carried out to this point.…”
Section: Ch 3mentioning
confidence: 99%
“…The ABC-DC algorithm was proposed by Picchini et al [ 25 ], and it uses ABC Markov chain Monte Carlo [ 33 ]. The algorithm works in two stages first the acceptance threshold, ε , is decreased according to a tolerance scheme { ε 1 , ε 2 , … , ε P }, and then the number of clones, K , is increased according to a clone scheme { K P +1 , K P +2 , … , K P + Q }, where subscripts index the population number.…”
Section: Methodsmentioning
confidence: 99%